Is specialization a strategy to improve farm efficiency in northwest China?. Issue 3 (26th May 2021) - Liu, Weiying; Shankar, Sriram; Li, Lihua
Abstract: Smallholders' specialization and commercialization is a way out of poverty and has been an important policy recommendation for countries in the early stages of structural change. However, the promotion of specialized commercial farming remains controversial. This study ascertains whether specialization is a strategy for improving efficiency based on a sample of smallholders in northwest China. A two‐step approach was employed to examine the relationship between production specialization and various efficiency measures. The nonparametric production frontier method of data envelopment analysis (DEA) was used to derive input‐based efficiency measures, followed by the tobit estimation to identify the inefficiency determinants. The econometric analysis results confirm that specialization increases households' technical efficiency (TE). However, in this study, we also find that specialization does not have a statistically significant impact on either the allocative or scale efficiency of the household. Food‐secure households are likely to be technically efficient, but TE is hindered by the external migration of more productive workers. Given the low estimates of farm efficiency in this study, policies facilitating labor markets and providing services for technical support and insurance should be implemented to encourage households to specialize in high‐value activities and integrate into markets.